Peran Perempuan di Desa Wisata Hijau Bilebante terhadap Pariwisata Berkelanjutan - Cahyani, Fathiya Agmariyan; Safira, Kania Salsa; Putra, Ilhamsyah Nur Utama; Nurhalizah, Aklesia; Ayu, Jati Paras (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
Tourism is the main source of revenue for the people of Lombok Island, particularly in Desa Wisata Hijau Bilebante. This village may be found in the Central Lombok Regency of West Nusa Tenggara. Beautiful rice fields and various intriguing activities can be found at Bilebante Green Tourism Village. Furthermore, Bilebante Green Tourism Village provides a selection of distinctive snacks administered by women. The purpose of this study is to determine the role of women in the development of Bilebante Green Tourism Village for sustainable tourism. Women are vital to the village's development as local leaders and as key players in economic operations, environmental protection, cultural preservation, and social empowerment. In qualitative terms, the research methods used in this study are descriptive and verification. According to the findings of this study, women play an important role in the development of the village, not only as local leaders but also as key players in economic activities, environmental protection, cultural preservation, and social empowerment. Suggestions for the development of Bilebante Green Tourism Village include improving the cleanliness of homestays, using environmentally friendly snack packaging, and providing road markings to improve tourist safety. Keywords: tourist village, Bilebante green tourism village, sustainable tourism, role of women